Оптимизация профиля промывочных насадок породорозрушающих инструментов - Ширали, И.Я. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The problem of profile optimization of the nozzles of washing system of rotation drilling rockdestruction tools has been set up and solved. The principle of maximum of pontryajm optimization method has been applied for optimization procedures. According to the investigation results optimum form of inner surface of washing nozzles of bits providing their maximum trydromonetoring efficiency and wear stability has been determined.